Benchmarking in the Contemporary Management System ("Journal "U". Economy. Management. Finance.", 2021)
The problem of enterprise development, optimization of its processes is constantly faced by the modern manager. And to solve some types of problems, you can apply a well-known management method - benchmarking as a process of using best practices.
Keywords: benchmarking; the main types of benchmarking; the possibilities of using benchmarking